Presence of onconeural antibodies in sarcoidosis patients with parasarcoidosis syndrome - Lower, Elyse; Sturdivant , Madison; Baughman, Robert P. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Bothersome symptoms from sarcoidosis can develop in the absence of identified granulomas.  These parasarcoidosis complaints can include small fiber neuropathy, diaphoresis, dysautonomia, and fatigue. Similar issues are also encountered in some cancer patients, especially those with onconeural antibodies. Methods: Serum was obtained for onconeural antibody testing from sarcoidosis patients with parasarcoidosis symptoms seen at the University of Cincinnati Sarcoidosis clinic during a six month period. Detection of antibodies was performed using an onconeural antibody panel. Results: A total of 268 patients with sarcoidosis and one or more features suggesting parasarcoidosis symptoms were enrolled in the study. Of these, 60 (22.4%) had one or more positive onconeural antibodies. In a control group of 46 non sarcoidosis patients seen in the interstitial lung disease clinic, there were only three patients with a positive antibody (Chi square=6.143, p=0.0132). A subgroup of sarcoidosis and control patients completed the small fiber neuropathy screening list. Sarcoidosis patients had a significantly higher score than the control patients (sarcoidosis: 7 [0-49] (Median [range] versus non sarcoidosis: 3 [0-31], p=0.0074). However, no significant differences were measured in the SFNL scores for sarcoidosis patients with an onconeural  antibody (9 [3-36]) versus without (7 [0-49]). Conclusion: In patients with parasarcoidosis symptoms, approximately 30% have evidence of onconeural antibody production.  This may be a potential cause for parasarcoidosis  symptoms in some patients.